The atypical chemokine receptor 2 reduces T cell expansion and tertiary lymphoid tissue but does not limit autoimmune organ injury in lupus-prone B6lpr mice - Xia, Wenkai; Eltrich, Nuru; Vielhauer, Volker (Frontiers in Immunology, 2024)
Introduction The atypical chemokine receptor 2 (ACKR2) is a chemokine scavenger receptor, which limits inflammation and organ damage in several experimental disease models including kidney diseases. However, potential roles of ACKR2 in reducing inflammation and tissue injury in autoimmune disorders like systemic lupus erythematosus (SLE) and lupus nephritis are unknown, as well as its effects on systemic autoimmunity. Methods To characterize functional roles of ACKR2 in SLE, genetic Ackr2 deficiency was introduced into lupus-prone C57BL/6lpr (Ackr2-/- B6lpr) mice. Results Upon inflammatory stimulation in vitro, secreted chemokine levels increased in Ackr2 deficient tubulointerstitial tissue but not glomeruli. Moreover, Ackr2 expression was induced in kidneys and lungs of female C57BL/6lpr mice developing SLE. However, female Ackr2-/- B6lpr mice at 28 weeks of age showed similar renal functional parameters as wildtype (WT)-B6lpr mice. Consistently, assessment of activity and chronicity indices for lupus nephritis revealed comparable renal injury. Interestingly, Ackr2-/- B6lpr mice showed significantly increased renal infiltrates of CD3+ T and B cells, but not neutrophils, macrophages or dendritic cells, with T cells predominantly accumulating in the tubulointerstitial compartment of Ackr2-/- B6lpr mice. In addition, histology demonstrated significantly increased peribronchial lung infiltrates of CD3+ T cells in Ackr2-/- B6lpr mice. Despite this, protein levels of pro-inflammatory chemokines and mRNA expression of inflammatory mediators were not different in kidneys and lungs of WT- and Ackr2-/- B6lpr mice. This data suggests compensatory mechanisms for sufficient chemokine clearance in Ackr2-deficient B6lpr mice in vivo. Analysis of systemic autoimmune responses revealed comparable levels of circulating lupus-associated autoantibodies and glomerular immunoglobulin deposition in the two genotypes. Interestingly, similar to kidney and lung CD4+ T cell numbers and activation were significantly increased in spleens of Ackr2-deficient B6lpr mice. In lymph nodes of Ackr2-/- B6lpr mice abundance of activated dendritic cells decreased, but CD4+ T cell numbers were comparable to WT. Moreover, increased plasma levels of CCL2 were present in Ackr2-/- B6lpr mice, which may facilitate T cell mobilization into spleens and peripheral organs. Discussion In summary, we show that ACKR2 prevents expansion of T cells and formation of tertiary lymphoid tissue, but is not essential to limit autoimmune tissue injury in lupus-prone B6lpr mice.